Go serverless with Google. (O'Reilly Media, Inc., 2019)
Serverless technology is among the fastest growing trends today in applications development and operations. But its name belies a simple fact: servers haven't gone away at all. Today, we have the option to "rent" server implementations from cloud providers that activate on demand rather than running in a persistent server. Among other things, this means that your organization no longer needs to concern itself with purchasing, provisioning, and maintaining physical servers. The benefits are manifold--too many to list here--but it does require a different approach to how we design and build applications to fully take advantage of the serverless paradigm. In this video course, aimed at intermediate- and advanced-level developers, your host, Martin Omander, a member of Google's Developer Relations team, shows you how to build reliable applications with serverless technology. You'll begin with a discussion of serverless fundamentals. Next, you examine how to design and create applications that are optimized for the serverless environment, including adopting microservices architectures that best exploit the serverless schema so that your applications function reliably in a user-facing production environment. This video course uses the Cloud Run Google Cloud service for examples; Cloud Run is currently in an open beta, and you will be able to use it as part of your exploration. In addition to conventional tutorial, Martin employs "Story Mode," in which you follow a startup as it builds a system for letting apartment complex managers connect with their tenants. When you've completed this video course, you'll have a solid understanding of the serverless model and a firm foundation on which to continue your serverless journey. What you'll learn--and how you can apply it What a serverless architecture is and how it is used Understand the benefits of a cloud-native serverless infrastructure and how your organization can best take advantage of it How to build a database-driven cloud application using serverless microservices This video course is for you because... You're an application developer working on a lean project. You're an application developer eager to apply the new serverless technology You're an experienced client-server developer looking for a different perspective You're a software engineering manager evaluating different technology for a project Prerequisites: You should have experience using a web-based development environment You should have experience using Node.js or Python (Node.js preferred) Materials or downloads needed in advance: None.